Characteristic Distribution Pattern of CD30-positive Cytotoxic T Cells Aids Diagnosis of Kikuchi-Fujimoto Disease. Issue 4 (April 2018) - Tabata, Tetsuya; Takata, Katsuyoshi; Miyata-Takata, Tomoko; Sato, Yasuharu; Ishizawa, Shin; Kunitomo, Tomoyoshi; Nagakita, Keina; Ohnishi, Nobuhiko; Taniguchi, Kohei; Noujima-Harada, Mai; Maeda, Yoshinobu; Tanimoto, Mitsune; et al.
Abstract : Introduction: Histiocytic necrotizing lymphadenitis (or Kikuchi-Fujimoto disease) frequently occurs in Asian young adult females and typically presents as cervical lymphadenopathy with unknown etiology. Although large immunoblasts frequently appear in Kikuchi-Fujimoto disease, the diffuse infiltration of these cells can cause difficulty in establishing a differential diagnosis from lymphoma. In such cases, CD30 immunostaining may be used; however, the extent or distribution pattern of CD30-positive cells in Kikuchi-Fujimoto disease remains largely unknown. Here we investigated the expression of CD30 and its clinicopathologic significance. Materials and Methods: We investigated 30 Kikuchi-Fujimoto disease and 16 control [6, systemic lupus erythematosus (SLE); 10, reactive lymphoid hyperplasia (RLH)] cases. Results: The number of CD30-positive cells in Kikuchi-Fujimoto disease was significantly more than that in SLE and RLH, and majority of these cells were located around necrotic areas. Moreover, double immunohistochemical staining showed these CD30-positive cells to be CD8-positive cytotoxic T cells, suggesting that activated cytotoxic T cells around necrotic areas are a characteristic feature of this disease. Clinicopathologic analysis showed that cases with abundant CD30-positive cells were predominantly female with only mild symptoms and normal laboratory data. Conclusions: In Kikuchi-Fujimoto disease cases, CD30-positive cytotoxic T cells were abundant around necrotic areas; this histologic feature may be helpful to differentiate this disease from SLE and RLH. Abstract : Supplemental Digital Content is available in the text.